Domestic Violence as a Cancellation of Inheritance Rights: An Analysis of Article 173 of the Compilation of Islamic Law Perspective of the Shafi'i School - Wilda Masna Sholihah; Winning Son Ashari (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2025)
Domestic violence (DV) is one of the most prevalent forms of human rights violations in Indonesia. In Chapter 173 of the Compilation of Islamic Law (KHI), it is stipulated that a person is barred from becoming an heir if they are proven, based on a final and binding court decision, to have committed murder, attempted murder, severe abuse, or slander against the deceased. Although the term “domestic violence” is not explicitly mentioned, several forms of domestic violence may meet the elements specified in the article. This study examines the status of domestic violence as a nullifier of inheritance rights from the perspective of Article 173 of the Compilation of Islamic Law (KHI) and the Shafi'i school of thought. The objective of this study is to analyze and identify the concept of domestic violence as a nullifier of inheritance rights based on Article 173 of the KHI and the Shafi’i school of thought’s perspective on domestic violence as a nullifier of inheritance rights. This study employs a qualitative approach with a literature review methodology. Research results indicate that acts of domestic violence (KDRT) that constitute murder, attempted murder, serious assault, or defamation against heirs, with a final and binding court decision, can prevent the perpetrator from obtaining inheritance rights, provided that the criminal acts meet the specified qualifications and the criminal penalties are in accordance with the provisions. However, this determination remains subject to the judge's decision and must not be made arbitrarily. In the Shafi'i school of thought, the obstacles to inheritance rights that are explicitly recognized are murder in any form, differences in religion, slavery, differences in status of unbelief, apostasy, and ad-daur al-hukmi, so that domestic violence only becomes an obstacle to inheritance if the act reaches the level of murder of the heir.